Gender discrimination and personal and professional development fostered by allopathic medical schools in the United States - Shruthi Venkataraman; Mytien Nguyen; Sarwat I. Chaudhry; Mayur M. Desai; Tonya L. Fancher; Alexandra M. Hajduk; Hyacinth R. C. Mason; Alexis Webber; Dowin Boatright (PLoS ONE, 2026)
Background Despite prevalent gender discrimination in medical education, its influence on personal and professional development, foundational competencies in medical training per the Association of American Medical Colleges (AAMC), remains unclear. This retrospective cross-sectional study assesses how experiences of gender discrimination in medical school influence personal and professional identity formation (PPIF) among males and females. Methods Deidentified student-level data were procured from the AAMC data warehouse for 37,610 MD students who matriculated in 2014–2015 and took the Graduation Questionnaire (GQ) between 2016–2020. Gender discrimination frequency was categorized as ‘Never’, ‘Isolated’, and ‘Recurrent’ from GQ responses to questions about denial of opportunities, offensive remarks, and lower evaluations due to gender. Students self-reported their sex as male, female or declined to answer. PPIF was assessed using two separate GQ metrics assessing student agreement on a 5-point Likert scale that their medical school fostered and nurtured their development as a person and a future physician, respectively, and dichotomized. Results Female students experienced higher rates of isolated (12.6%) and recurrent (20.1%) gender discrimination than males (4.3% isolated, 6.2% recurrent). Females reported slightly lower personal (71.2%) but similar professional development (92.2%) rates compared to males (73.4% personal, 91.2% professional). Both sexes experiencing gender discrimination had lower likelihoods of PPIF than their counterparts without these experiences. If recurrent discrimination occurred, the aRR (95%CI) of professional development was 0.89 (0.87–0.90) for females and 0.78 (0.74–0.81) for males, while for personal development, it was 0.69 (0.67–0.71) for females and 0.61 (0.58–0.66) for males. Compared to females, males showed sharper declines in professional development as discrimination frequency increased from never to isolated (aRR = 0.93, 95% CI [0.92–0.94], p < 0.001) and isolated to recurrent (aRR = 0.95, 95% CI [0.93–0.97], p < 0.001). Conclusions Gender discrimination negatively influences PPIF for both female and male medical students. Efforts to combat discrimination in medical training and promote holistic student development should be considered. Future work is needed to understand the influence of gender discrimination on the comprehensive development of gender-diverse medical students.